2024
DOI: 10.1002/jqs.3592
|View full text |Cite
|
Sign up to set email alerts
|

Late MIS5a in the southern North Sea: new chronostratigraphic insights from the Brown Bank Formation

Irene M. Waajen,
Freek S. Busschers,
Timme H. Donders
et al.

Abstract: The Brown Bank Formation (BB Fm) is a clay‐rich sedimentary unit that is distributed over a large area in the southern North Sea. It is easily recognisable in 2D acoustic reflection profiles, forming sets of subparallel high‐amplitude reflections. Previous studies have provided only fragmentary information on the facies, and a variety of interpretations on the depositional environment and age of the BB Fm. In this study we combine high‐resolution 2D acoustic reflection profiles and multiproxy sedimentological,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 51 publications
1
16
1
Order By: Relevance
“…The depositional setting of the BB Fm was previously interpreted as either freshwater dominated (Oele, 1971), or transitional from brackish lagoonal to freshwater (Cameron et al, 1989;Zagwijn, 1983). More recently, it has been interpreted to represent a shallow-marine depositional setting with high terrestrial input (Eaton et al, 2020;Laban, 1995;Waajen et al, 2024). Several depositional phases in the BB Fm are distinguished on 2D high-resolution seismic profiles (Eaton et al, 2020;Missiaen et al, 2021, Waajen et al, 2024.…”
Section: Brown Bank Formation and Site Descriptionmentioning
confidence: 99%
See 4 more Smart Citations
“…The depositional setting of the BB Fm was previously interpreted as either freshwater dominated (Oele, 1971), or transitional from brackish lagoonal to freshwater (Cameron et al, 1989;Zagwijn, 1983). More recently, it has been interpreted to represent a shallow-marine depositional setting with high terrestrial input (Eaton et al, 2020;Laban, 1995;Waajen et al, 2024). Several depositional phases in the BB Fm are distinguished on 2D high-resolution seismic profiles (Eaton et al, 2020;Missiaen et al, 2021, Waajen et al, 2024.…”
Section: Brown Bank Formation and Site Descriptionmentioning
confidence: 99%
“…More recently, it has been interpreted to represent a shallow-marine depositional setting with high terrestrial input (Eaton et al, 2020;Laban, 1995;Waajen et al, 2024). Several depositional phases in the BB Fm are distinguished on 2D high-resolution seismic profiles (Eaton et al, 2020;Missiaen et al, 2021, Waajen et al, 2024. Initially, pollen studies suggested deposition occurred around late MIS 5e and MIS 5d (Laban & Mesdag, 1995;Zagwijn, 1983), while luminescence ages from vibrocores show a range between 85 and 55 ka, corresponding to MIS 5a -MIS 3 (Limpenny et al, 2011;Wessex Archaeology, 2018, Waajen et al, 2024.…”
Section: Brown Bank Formation and Site Descriptionmentioning
confidence: 99%
See 3 more Smart Citations